1982
DOI: 10.1128/aac.21.5.773
|View full text |Cite
|
Sign up to set email alerts
|

Structural and phenotypic varieties of gentamicin resistance plasmids in hospital strains of Staphylococcus aureus and coagulase-negative staphylococci

Abstract: We previously described a neonatal nursery epidemic of infections caused by a single strain of Staphylococcus aureus bearing a gentamicin resistance plasmid (Vogel et al., Antimicrob. Agents Chemother. 13:466-472, 1978

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 14 publications
2
57
0
Order By: Relevance
“…The MGRSA strains isolated in Dublin differ from similar S. aureus strains that have been reported from France, Australia, the UK and the USA (Soussy et al, 1975;Shanson et al, 1976;Crossley et al, 1979;McGowan et al, 1979;Price et al, 1980;Jaffe et al, 1982;Archer and Mayhall, 1983;Lyon et al, 1983;Naidoo et al, 1983;Townsend et al, 1983a) by invariably exhibiting chromosomal resistance to gentamicin. In strains reported from the USA, resistance to gentamicin is often encoded by large conjugative plasmids (Archer and Johnston, 1983;Forbes and Schaberg, 1983;McDonnell et al, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…The MGRSA strains isolated in Dublin differ from similar S. aureus strains that have been reported from France, Australia, the UK and the USA (Soussy et al, 1975;Shanson et al, 1976;Crossley et al, 1979;McGowan et al, 1979;Price et al, 1980;Jaffe et al, 1982;Archer and Mayhall, 1983;Lyon et al, 1983;Naidoo et al, 1983;Townsend et al, 1983a) by invariably exhibiting chromosomal resistance to gentamicin. In strains reported from the USA, resistance to gentamicin is often encoded by large conjugative plasmids (Archer and Johnston, 1983;Forbes and Schaberg, 1983;McDonnell et al, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…In addition to GTKR, these transformants also acquired ethidium bromide resistance (EbR), a character that has been reported to be encoded on some gentamicin-resistance plasmids (Jaffe et al, 1982;McDonnell et al, 1983). In contrast to these GTKR-EbR transformants that carried pSK 1, GTKR transformants were obtained that lacked pSKl and failed to gain EbR.…”
Section: Plasmid Dna Projiles and Location Of Resistance Determinantsmentioning
confidence: 78%
“…aureus has most frequently been reported to be plasmid-mediated (Soussy et al, 1975;Wood, Carter and Best, 1977;Cohen et al, 1982;Jaffe et al, 1982;McDonnell et al, 1983), although chromosomally-encoded resistance has recently been observed in Australia (Lyon et al, 1983;Townsend, et al, 1983) and elsewhere (Kayser, Homberger and Devaud, 1981;Dowd, Cafferkey and Dougan, 1983). Among the strains isolated at this hospital, aminoglycoside resistance was suspected to be chromosomally encoded in the majority of isolates before 1980.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaffe et al (1982) report the presence of large plasmids in strains of CNS resistant to gentamicin. Also gentamicin resistance has been found to be encoded on the transposon Tn4001 in staphylococcal species (Lyon, May & Skurray, 1984 PDF isolates from ten patients had plasmid profiles which clearly (lifferentiated them from body-site isolates.…”
Section: Plasmid Profilesmentioning
confidence: 99%